Thermo-Economic Optimization of Heliostat Field Distribution Considering Magnitude and Aspect Ratio of Heliostat Using Multiobjective Gray Wolf Optimizer (Case Study: Tehran) - Shahbazi, Mona; Javaherdeh, Kourosh; Naghashzadegan, Mohammad (Mechanical Technology and Engineering Insights, 2025)
This study aims to investigate the effect of heliostat geometry on the performance of a heliostat field. Rectangular reflectors, as a prevalent type of heliostats, were surveyed. The heliostat's aspect ratio significantly affects the shading and blocking factors, ultimately altering the optical efficiency of the heliostat field. The Multiobjective Gray Wolf Optimizer (MOGWO) is used to design a heliostat field composed of heliostats with optimal aspect ratios. The goal is to achieve maximum optical efficiency with the lowest Levelised Cost Of Energy (LCOE). The results indicate that optimizing the heliostat aspect ratio alone increases optical efficiency by 5.2%. However, the simultaneous optimization of the reflectors and the heliostat field can improve optical efficiency by 11%.